2003
DOI: 10.1061/(asce)0733-9445(2003)129:10(1322)
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Analysis of Axially Loaded Concrete-Filled Tube Columns with Confinement Effect

Abstract: Proper material constitutive models for concrete-filled tube ͑CFT͒ columns are proposed and verified by the nonlinear finite element program ABAQUS against experimental data. The cross sections of the CFT columns in the numerical analysis are categorized into three groups, i.e., circular section, square section, and square section stiffened by reinforcing ties. Via the numerical analyses, it is shown that for circular CFT columns, the tubes can provide a good confining effect to the concrete especially when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
329
0
26

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(396 citation statements)
references
References 16 publications
(10 reference statements)
2
329
0
26
Order By: Relevance
“…Concrete Filled Tube (CFT) structures are widely used in engineering due to their excellent structural and constructional performance [1,2]; this is especially the case for typical forms of Concrete Filled Steel Tube (CFST) structures [3][4][5][6][7][8][9][10]. Attention also has been paid to Concrete Filled Fiber Reinforced Polymer (FRP) Tubes, in view of their anti-corrosion properties, which can be better adapted to corrosive environments than CFST [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete Filled Tube (CFT) structures are widely used in engineering due to their excellent structural and constructional performance [1,2]; this is especially the case for typical forms of Concrete Filled Steel Tube (CFST) structures [3][4][5][6][7][8][9][10]. Attention also has been paid to Concrete Filled Fiber Reinforced Polymer (FRP) Tubes, in view of their anti-corrosion properties, which can be better adapted to corrosive environments than CFST [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several existing constitutive models for CFST concrete under axial load (Hatzigeorgiou, 2008;Hu et al, 2003;Liang and Fragomeni, 2009), they may not predict the capacity of CFSTs under eccentric load accurately. Investigation of the analysis method for eccentrically loaded CFST columns proposed by Liang (2011), which incorporates the identical concrete model for the axial loading case from Liang and Fragomeni (2009), revealed that the method overestimates the capacity of eccentric loading on 87 specimens by 6% on average.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the fact that the real-time pressure in a CFST column is difficult to trace, it is reasonable to analyse the flexural behaviour of a CFST by a constant confining pressure throughout the loading process (Hajjar et al, 1998;Hatzigeorgiou, 2008). Subsequently, many different empirical equations have been developed to correlate the pressure with various material properties and geometry of the cross-section of CFST columns (Hatzigeorgiou, 2008;Hu et al, 2003;Tang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Schneider (1998) and Hu et al (2003) developed a three-dimensional (3D) nonlinear finite element model (FEM) for CFT circular columns, in which the ABAQUS program was used. The concrete confinement was achieved by matching the numerical results by trial and error using a parametric study.…”
Section: Introductionmentioning
confidence: 99%